Contagion in the stock markets: the 2007 subprime financial crisis. (7th April 2011) - Jayech, Selma; Sadraoui, Tarek; Zina, Naceur Ben
In this article, we test the presence of financial contagion during the subprime mortgage crisis of 2007. For this purpose, we propose a new procedure for testing the non-linearity of the mechanisms of the shock distribution estimated through a model of long-term interdependence. We apply this methodology to the stock markets. Our empirical study shows the contamination of France, Germany, the UK and Japan.